2015
DOI: 10.1088/0004-637x/809/2/184
|View full text |Cite
|
Sign up to set email alerts
|

R Coronae Borealis Stars Are Viable Factories of Pre-Solar Grains

Abstract: We present a new theoretical estimate for the birthrate of R Coronae Borealis (RCB) stars that is in agreement with recent observational data. We find the current Galactic birthrate of RCB stars to be ≈ 25% of the Galactic rate of Type Ia supernovae, assuming that RCB stars are formed through the merger of carbon-oxygen and helium-rich white dwarfs. Our new RCB birthrate (1.8 × 10 −3 yr −1 ) is a factor of 10 lower than previous theoretical estimates. This results in roughly 180-540 RCB stars in the Galaxy, de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 65 publications
6
24
1
Order By: Relevance
“…Qualitatively, one can link this to rotation and other processes in the merger. An extension of this work to lower metallicity (Menon et al 2019) finds 16 O/ 18 O and 12 C/ 13 C ratios consistent with observed R CrBs and also with the possibility that these stars are the sources of some graphitic grains (Karakas et al 2015). The R CrB models of Lauer et al (2019) also use initial conditions motivated by WD mergers.…”
Section: Review Of Previous Worksupporting
confidence: 71%
“…Qualitatively, one can link this to rotation and other processes in the merger. An extension of this work to lower metallicity (Menon et al 2019) finds 16 O/ 18 O and 12 C/ 13 C ratios consistent with observed R CrBs and also with the possibility that these stars are the sources of some graphitic grains (Karakas et al 2015). The R CrB models of Lauer et al (2019) also use initial conditions motivated by WD mergers.…”
Section: Review Of Previous Worksupporting
confidence: 71%
“…There are only 5 low-gravity He-sdO stars and 4 O(He) stars known (Jeffery 2008a). Population synthesis calculations indicate an RCB birthrate ∼10 −2 -10 −3 yr −1 (Han 1998;Nelemans et al 2001;Tisserand et al 2013;Zhang et al 2014;Karakas et al 2015;Yungelson & Kuranov 2016;Brown et al 2016). RCB stars are thought to be ∼0.8-0.9 M from pulsation modeling (Saio 2008), and this mass agrees well with the predicted mass of the merger products of a CO-and a He-WD (Han 1998).…”
Section: Lifetimes and The Expected Number Of Rcb Starssupporting
confidence: 61%
“…Using a value of 0.0018 yr −1 for the birthrate of RCB stars (Karakas et al 2015), we can estimate the number of RCB and EHe stars in the Galaxy by multiplying this value times their typical lifetimes. Table 4 gives the lifetimes as RCB stars (t 2 ∼ 10 5 yr) and the lifetimes of the EHe stars (t 3t 2 ∼ 10 4 yr) as calculated by our MESA models.…”
Section: Lifetimes and The Expected Number Of Rcb Starsmentioning
confidence: 99%
“…This result is in excellent agreement with theoretical estimates made from population synthesis. Indeed, with He-CO white dwarfs merger birthrate ranging between ∼ 10 −3 and ∼ 5×10 −3 per year (Nelemans et al 2001;Ruiter et al 2009;Karakas et al 2015) and an RCB phase lifetime of about 10 5 years, as predicted by theoretical evolution models (Saio & Jeffery 2002;Lauer et al 2018), the expected theoretical number of Galactic RCB stars range between 100 and 500. These estimates are also consistent between the Milky Way and the Magellanic Clouds.…”
Section: How Many Galactic Rcb Stars Exist Out There?mentioning
confidence: 92%